Principles of fluorescence spectroscopy - Lakowicz, Joseph (Springer, 2006)
The third edition of this established classic text reference builds upon the strengths of its very popular predecessors. Organized as a broadly useful textbook Principles of Fluorescence Spectroscopy, 3rd edition maintains its emphasis on basics, while updating the examples to include recent results from the scientific literature. The third edition includes new chapters on single molecule detection, fluorescence correlation spectroscopy, novel probes and radiative decay engineering. Includes a link to Springer Extras to download files reproducing all book artwork, for easy use in lecture slides. This is an essential volume for students, researchers, and industry professionals in biophysics, biochemistry, biotechnology, bioengineering, biology and medicine.